Adrenal vein sampling in primary aldosteronism: concordance of simultaneous vs sequential sampling. Issue 2 (February 2017) - Almarzooqi, Mohamed-Karji; Chagnon, Miguel; Soulez, Gilles; Giroux, Marie-France; Gilbert, Patrick; Oliva, Vincent L; Perreault, Pierre; Bouchard, Louis; Bourdeau, Isabelle; Lacroix, André; Therasse, Eric
Abstract : Objective: Many investigators believe that basal adrenal venous sampling (AVS) should be done simultaneously, whereas others opt for sequential AVS for simplicity and reduced cost. This study aimed to evaluate the concordance of sequential and simultaneous AVS methods. Design and methods: Between 1989 and 2015, bilateral simultaneous sets of basal AVS were obtained twice within 5 min, in 188 consecutive patients (59 women and 129 men; mean age: 53.4 years). Selectivity was defined by adrenal-to-peripheral cortisol ratio ≥2, and lateralization was defined as an adrenal aldosterone-to-cortisol ratio ≥2, the contralateral side. Sequential AVS was simulated using right sampling at −5 min ( t  = −5) and left sampling at 0 min ( t  = 0). Results: There was no significant difference in mean selectivity ratio ( P  = 0.12 and P  = 0.42 for the right and left sides respectively) and in mean lateralization ratio ( P  = 0.93) between t  = −5 and t  = 0. Kappa for selectivity between 2 simultaneous AVS was 0.71 (95% CI: 0.60–0.82), whereas it was 0.84 (95% CI: 0.76–0.92) and 0.85 (95% CI: 0.77–0.93) between sequential and simultaneous AVS at respectively −5 min and at 0 min. Kappa for lateralization between 2 simultaneous AVS was 0.84 (95% CI: 0.75–0.93), whereas it was 0.86 (95% CI: 0.78–0.94) and 0.80 (95% CI: 0.71–0.90) between sequential AVS and simultaneous AVS at respectively −5 min at 0 min. Conclusions: Concordance between simultaneous and sequential AVS was not different than that between 2 repeated simultaneous AVS in the same patient. Therefore, a better diagnostic performance is not a good argument to select the AVS method.